“I Will Come Like a Thief” (Rev 3:3, 16:15) - József NAGY (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2023)
This paper examines the motif of the thief in Revelation 3:3 and 16:15. These verses are analysed in the light of other New Testament occurrences and possible Old Testament parallels. With this in mind, the first part of the paper deals with the parable of the thief (Mt 24:43–44; Lk 12:39–40). Since there has been a growing interest in recent decades in the study of the relationship between Revelation and the Synoptic Gospels, we will briefly review the history of this research. In the light of this, the second half of the study takes up an exegetical problem in both Revelation 3:3 and 16:15. We argue that Revelation 3:3, like other instances of the motif in the New Testament, testifies to the return of Christ. In the case of Revelation 16:15, a careful examination of the thief motif makes it possible to maintain that the verse is an integral part of the unit. This is confirmed, among other things, by the fact that the thief motif and the Day of the Lord are found in the same context (Rev 16:14–15; cf. 1 Thess 5:2.4; 2 Pet 3:10).